ACCOMPLISHMENTS AND FUTURE OF BIOLOGICAL CONTROL AND INTEGRATED CONTROL IN BRAZIL – PART 2 - Sverre Hagen, Kenneth (REVISTA DE AGRICULTURA, 2024)
The introductions of natural enemies against Homoptera in the world have been particularly successful. Already in Brazil there have been 5 or 6 homopterous pests brought under partial to complete control by introduced natural enemies and these species are indicated by an asterisk before their names in the list, but there are nearly 90 species of Homoptera that apparently have been introduced which possess natural enemies that are not recorded to be in Brazil (see list). Some outstanding natural enemies that should be considered for introduction against homopterous pests in Brazil are noted in the list.